Physical Attractiveness as a Signal of Biological Quality - Rantala, Markus J. (fi=Turun yliopisto|en=University of Turku|, 2014)
It has been commonly thought that standards of beauty are arbitrary cultural conventions that vary between cultures and time. In my thesis I found that it is not so. Instead, I show that attractiveness and preferred traits serve as cues to phenotypic qualities that provide selective benefits for those who choose their mates based on these criteria. In the first study I show that attractive men have a stronger antibody response to the hepatitis b vaccine and higher levels of testosterone than their less attractive peers. Men with low levels of testosterone also tend to have high levels of the stress hormone cortisol, suggesting that their immune responses may have been inhibited by stress hormones. Thus, facial attractiveness may serve as an honest cue of the strength of immune defence in men. In the second study, I show that the attractiveness of the male body is also a cue of better immunity. In addition, I show that adiposity, both in men’s faces and bodies, is a better cue of the strength of immunity and attractiveness than of masculinity. In the third study, I test the preferences of women from 13 countries for facial cues of testosterone and cortisol. I show that there is cross-cultural variation in women’s preference for cues of testosterone and cortisol in male faces. I found a relationship between the health of a nation and women’s preferences for cues of testosterone in the male face and the interaction between preferences for cues of testosterone and cortisol. I show also a relationship between preferences for cues of testosterone and a societal-level measure of parasite stress. Thus, it seems that societal-level ecological factors influence the relative value of traits as revealed by combinations of testosterone and stress hormones. In the fourth study, I show that women’s immune responsiveness (amount of antibodies produced) does not predict facial attractiveness. Instead, plasma cortisol level is negatively associated with attractiveness, indicating that stressed women look less attractive. Fat percentage is curvilinearly associated with facial attractiveness, indicating that being too thin or too fat reduces attractiveness. This study suggests that in contrast to men, facial attractiveness in women does not indicate the strength of immune defence, but is associated with other aspects of long-term health and fertility: circulating levels of the stress hormone cortisol and the percentage of body fat. In the last study I show that the attractiveness of men’s body odor is positively correlated with stress hormone levels, suggesting also that the attractiveness of body odors may signal the phenotypic quality of males to females. However, the attractiveness of men’s body odor was not associated with testosterone levels. My thesis suggests that the standard of beauty is not in the eye of the beholder. Instead, our standard of beauty is hardwired in our brains by genes that are selected by natural selection and also influenced by current environmental conditions.

Lukuisat viimeaikaiset tutkimukset evoluutiopsykologian alalla ovat osoittaneet että kasvojen ja vartalon puoleensavetävyydellä on huomattava vaikutus ihmisen parinvalinnassa. Evoluutiopsykologit olettavat, että fyysinen puoleensavetävyys kertoo henkilön fenotyyppisestä- tai geneettisestä laadusta pariutumiskumppanina, mutta mitä tämä laatu on ja miksi puoleensavetävyys olisi rehellinen signaali laadusta, on jäänyt epäselväksi ja kiistanalaiseksi. Väitöskirjani ensimmäisessä osatutkimuksessa selvitin miesten immuunijärjestelmän tehokkuuden yhteyttä miesten kasvojen puoleensavetävyyteen tutkimalla kuinka voimakkaasti miesten immuunijärjestelmä reagoi hepatiitti B -rokotteeseen tuottamalla vasta-aineita virusta vastaan. Kokeessa havaitsin että naiset arvioivat komeimmiksi miehiä, joilla oli voimakkain immuunivaste ja korkein testosteronitaso. Toisessa osatutkimuksessa havaitsin, että myös miesten vartalon puoleensavetävyys on yhteydessä immuunipuolustusjärjestelmän tehokkuuteen. Lisäksi havaitsin, että vartalon rasvaprosentti on voimakkaammin yhteydessä vartalon puoleensavetävyyteen ja immuunijärjestelmän tehokkuuteen kuin vartalon maskuliinisuus. Kolmannessa osakokeessa tutkin eroaako naisten mieltymys testosteronitasosta ja stressihormonitasosta kertoviin miesten kasvonpiirteisiin maantieteellisesti. Tutkimuksessa esitin 13 eri maassa naisille kuvia miesten kasvoista, joita oli manipuloitu testosteronista ja stressihormonista kertovien piirteiden suhteen. Kokeessa havaitsin että köyhissä maissa, joissa terveydenhuolto on huono naiset suosivat voimakkaammin testosteronista kertovia piirteitä kuin paremman terveydenhuollon omaavissa maissa. Tutkimus viittaa siihen, että ympäristöolosuhteet vaikuttavat siihen, millaisista miestenkasvoista naiset pitävät. Neljännessä osakokeessa tutkin kuvastaako naisen kasvojen puoleensavetävyys hänen immuunijärjestelmänsä toiminnan tehokkuutta. Havaitsin, että toisin kuin miehillä, naisilla kasvojen puoleensavetävyydellä ei ole yhteyttä hänen kykyyn tuottaa vasta-aineita hepatiitti B -rokotetta vastaan. Sen sijaan huomasin, että miehet suosivat naisia jolla on alhainen stressihormonitaso. Myös naisen rasvaprosentilla oli vaikutusta puoleensavetävyyteen. Sekä liian alhainen että liian korkea rasvaprosentti heikensi puoleensavetävyyttä. Aikaisempien tutkimusten perusteella tiedetään sekä liian alhaisen, että liian korkean rasvaprosentin heikentävän naisen hedelmällisyyttä. Korkean stressihormonitason tiedetään myös heikentävän naisen hedelmällisyyttä, joten tutkimusten valossa näyttäisi siltä, että miehet ovat sopeutuneet suosimaan naisten kasvoissa piirteitä jotka kuvastavat hedelmällisyyttä, mutta ei hyvää immuniteettikykyä. Viimeisessä osatutkimuksessani havaitsin, että miesten hajun puoleensavetävyys ei ole yhteydessä heidän testosteroni- ja estradiolitasoihinsa. Sen sijaan naiset suosivat sellaisten miesten ominaishajua joilla oli korkea stressihormonitaso koetilanteessa. Väitöskirjatutkimukseni viittaavat siihen, että fyysisellä puoleensavetävyydellä on vankka biologinen pohja, eikä kauneuskäsitys ole vain sosiaalisesti rakentunut mielivaltainen konstruktion, kuten monet humanistit väittävät